Ответ(ы) на вопрос:
[latex] 2)\; \; \sqrt{(\sqrt{16-6\sqrt7}+\sqrt7)\cdot 3} =\sqrt{(\sqrt{(3-\sqrt7)^2}+\sqrt7)\cdot 3}=\\\\=\sqrt{(|3-\sqrt7|+\sqrt7)\cdot 3}=\sqrt{(3-\sqrt7+\sqrt7)\cdot 3}=\sqrt{3\cdot 3}=3\\\\3)\; \; \sqrt{(\sqrt{8+2\sqrt{15}}-\sqrt{8-2\sqrt{15}})\cdot 2+7}=\\\\=\sqrt{(\sqrt{(\sqrt5+\sqrt3)^2}-\sqrt{(\sqrt5-\sqrt3)^2})\cdot 2+7}=\\\\=\sqrt{(|\sqrt5+\sqrt3|-|\sqrt5-\sqrt3|)\cdot 2+7}=\\\\=\sqrt{(\sqrt5+\sqrt3-\sqrt5+\sqrt3)\cdot 2+7}=\sqrt{2\sqrt3\cdot 2+7}=[/latex]
[latex]=\sqrt{7+4\sqrt3}=\sqrt{(2+\sqrt3)^2}=|2+\sqrt3|=2+\sqrt3[/latex]
Не нашли ответ?
Похожие вопросы